The Plague and the City as Forms of Absurdity - Alexander Rappaport (Проект Байкал, 2019)
Plague epidemics turned the city from the place of recovery to the place of death. The plague was neutralized by chemistry and came back immediately in the loss of the scale, growth in urban territories and roads, and emergence of awful city labyrinths.